Geometric max stability of random vectors - Aksomaitis, Algimantas; Ivanovienė, Irma (Lietuvos matematikos rinkinys, 2009)
Geometric max (min) stability of random variables is investigated enough. In this article, geometric stability concept is extended for the vectors. We also search connections between the geometric max (min) stability and max (min) stability of vectors.